Towards a Private Sector led Growth Model : Bosnia and Herzegovina Innovation and Entrepreneurship Assessment - Aridi, Anwar; Ong Lopez, Anne (World Bank, Washington, DC, 2019)
The growth landscape of Bosnia and Herzegovina (BiH) is undermined by adverse productivity developments and weak private sector development. BiH is still finding a pathway to rebalance its current public sector-led growth model to a private sector-led one. In this light, enhancing innovation and entrepreneurship (I and E) is a key priority for BiH. This report provides a comprehensive assessment of the current I and E landscape in BiH and offers a roadmap for innovation policy reforms. It showcases current I and E outcomes in BiH and provides analysis of whether current support policies and programs in BiH (including public budget allocations) address existing market failures. The report concludes that recent policy measures have not effectively addressed BiH's needs for supporting I and E, specifically in terms of access to skills, ease of business regulations, and predictability of business environment. To this end, this report offers a roadmap for policy reforms as well as suggestions for pilot programs.